Bandgap characteristics of a tensegrity metamaterial chain with defects. (April 2020) - Yin, Xu; Zhang, Shuai; Xu, Guang-Kui; Zhang, Li-Yuan; Gao, Zhi-Ying
Abstract: Mechanical metamaterials with tunable bandgaps are promising solutions for wave control and vibration mitigation under various frequency scales. For the metamaterials consisting of tensegrities, their bandgaps are currently regulated through the prestresses or loads. In this Letter, we propose a novel and powerful approach to tune the bandgap characteristics of tensegrity metamaterials by introducing structural defects. The metamaterial is constructed using truncated regular octahedral tensegrities (TROTs) and circular plates as elementary cells. An analytical model is established for evaluating the effective stiffness of TROT under uniaxial loads. Using both Bloch theorem-based simulations and frequency response tests, we show that the proposed chain without defects can hold a bandgap. Interestingly, we find that the introduction of structural defects leads to several flat branches within the bandgap, namely defect states . These defect states are localized and determined by the damage degree of cells and total number of damaged cells. The tensegrity metamaterials with designed defect states are expected to hold a variety of applications, for instance, in the fields of exploiting advanced isolators and novel filters.